ENTREPRENEURIAL INNOVATION WITHOUT RULES: HOW TRUST AND PLATFORMS BUILD UNREGULATED DIGITAL MARKETS - Wicaksono, Tutur; Prathivi, Maria Dini Gilang; Liem, Maria Christina (Jurnal Pengabdian dan Kewirausahaan, 2026)
Entrepreneurial innovation in unregulated digital commerce has become a significant driver of contemporary market formation, especially in contexts where digital transactions occur outside clearly defined regulatory frameworks and formal institutional governance. This study investigates how entrepreneurs convert institutional ambiguity into viable market opportunities through digital technologies, platform infrastructures, and trust-based mechanisms. Employing the SALSA framework, a systematic literature review was conducted across Scopus and Web of Science databases, identifying relevant peer-reviewed studies published between 2014 and 2025 on digital entrepreneurship, informal digital markets, platform governance, legitimacy formation, and trust-based mechanism. The findings indicate that entrepreneurial innovation in unregulated digital commerce is primarily driven by the substitution of formal institutions with social trust mechanisms, the adaptation of digital affordances into market devices, and the development of platform-based governance systems that reshape entrepreneurial power relations. Contrary to the assumption that regulatory absence necessarily undermines market stability, the review shows that unregulated digital markets often achieve functional stability through community norms, reputational systems, and platform-mediated coordination. However, these systems also create structural vulnerabilities related to governance asymmetry, legitimacy fragility, and long-term sustainability. This study contributes to the literature on entrepreneurship, marketing innovation, and digital technology by integrating institutional theory, digital entrepreneurship, and platform studies into a unified analytical framework. It provides practical insights for entrepreneurs, platform designers, and policymakers seeking to balance innovation flexibility with market stability in digitally mediated commerce.